Inactivated TZ84 strain hepatitis A vaccine and its impact: A narrative review - Yewale, Vijay; Marathe, Sanjay (Indian Journal of Child Health, 2024)
Hepatitis A (HepA) represents a significant global public health challenge. At present, there is no definitive treatment available for managing HepA. Before the availability of HepA vaccines, hepatitis A virus (HAV) infection had emerged as a leading cause of fulminant hepatic failure and a significant indication for liver transplantation in children living in Argentina, Brazil, the Republic of Korea, and India. Inactivated HAV vaccines have demonstrated a high level of immunogenicity. In addition, there is evidence supporting the use of inactivated HepA vaccines in immunocompromised individuals and as post-exposure prophylaxis. Recently, the inactivated TZ84 strain hepatitis A vaccine, which has shown superior immunogenicity for up to 30 years and fewer adverse reactions when compared with other inactivated HepA vaccines, has become available in India. Moreover, the TZ84 strain of the inactivated HAV vaccine has the potential to control community-wide outbreaks. This narrative review offers an overview of the existing evidence concerning immunization against HepA in India, with a particular emphasis on the TZ84 strain of the inactivated HAV vaccine.